Measurement of dabigatran plasma concentrations by calibrated thrombin clotting time in comparison to LC-MS/MS in human volunteers on dialysis. Issue 3 (March 2015) - Schmohl, Michael; Gansser, Dietmar; Moschetti, Viktoria; Stangier, Joachim
Abstract Introduction Dabigatran etexilate is an oral direct thrombin inhibitor. Although routine anticoagulation monitoring with dabigatran is not usually required, a simple and precise laboratory test to measure dabigatran concentrations in patient plasma may be useful in certain clinical circumstances, such as emergency situations. The HEMOCLOT® Thrombin Inhibitors assay has demonstrated accurate and precise determination of dabigatran concentrations within a range of 50–500 ng/ml. The objective of this study was to assess comparability of dabigatran concentrations determined by HEMOCLOT® and by liquid chromatography/tandem mass spectrometry (LC-MS/MS) in plasma samples from human volunteers with end-stage renal disease (ESRD) undergoing regular haemodialysis (HD) during a Phase I study. Materials and Methods Overall, 304 plasma samples were obtained from seven ESRD patients in dabigatran steady-state for measurement by HEMOCLOT® (calibrated diluted thrombin time [dTT]) and by LC-MS/MS. Agreement of dabigatran concentrations was assessed by regression analysis and difference plots. Results The measurements of calibration standards of the HEMOCLOT® assay showed excellent precision with coefficients of variation < 5%. Accuracy determined by analysis of two quality control samples was 90% and 111%. HEMOCLOT®-derived dabigatran plasma concentrations paralleled those obtained by LC-MS/MS. The mean ratio of the LC-MS/MS and dTT-derived concentrations was 0.955 (67% limits of agreement: 0.771–1.18). Conclusions The HEMOCLOT® Thrombin Inhibitors assay is suitable for measuring dabigatran plasma concentrations in volunteers with ESRD undergoing haemodialysis. The agreement between dabigatran concentrations determined by the HEMOCLOT® assay and the LC-MS/MS reference method met bioanalytical acceptance criteria.